Using web crawlers for feature extraction of social nets for analysis - Noor, Fozia; Shah, Asadullah; Gill, Waris; Ahmad Khan, Shoab (Springer Verlag, 2018)
This paper presents a crawler based feature extraction technique for social network analysis. This technique crawl a predefined actor and his associated activities in social network space. From the activities, a set of features are extracted that can be used for a broad spectrum of social network analysis. The utility can act as a middle ware providing a level of abstraction to researchers involved in social network analysis. The tools provide a formatted set of ready features with open APIs that can be easily integrated in any application. © Springer International Publishing AG 2018.